The biogenesis and biological roles of migrasomes in human diseases - Yifan Zhang; Wei Chen; Jiageng Zhu; Luwei Xu (Cell Death Discovery)
Abstract Migrasomes are recently identified extracellular vesicles that are specifically generated by migrating cells. These pomegranate-like, membrane-bound organelles are released at the trailing edge during cell migration and play crucial roles in cell-to-cell communication, intercellular signaling, and tissue remodeling. Migrasomes selectively package various molecular components, including proteins, lipids, and RNA, facilitating a unique form of cellular communication known as migracytosis. They are involved in numerous physiological and pathological processes, including immune responses, cancer metastasis, tissue repair, and embryonic development. In this review, we provide an in-depth analysis of the biogenesis, structural features, and molecular composition of migrasomes. We further explore the emerging roles of migrasomes in disease pathogenesis, particularly their potential in cancer, neurodegenerative diseases, and immune modulation. Overall, this review aims to offer comprehensive insights into the latest research on migrasomes, while addressing the challenges in their study and potential avenues for future clinical implementation.